Impact of MLC leaf width on volumetric‐modulated arc therapy planning for head and neck cancers. (8th November 2013) - Lafond, Caroline; Chajon, Enrique; Devillers, Anne; Louvel, Guillaume; Toublanc, Sandra; Olivier, Mickael; Simon, Antoine; de Crevoisier, Renaud; Manens, Jean‐Pierre
Abstract : This dosimetric study investigated the impact of multileaf collimators (MLC) leaf width in volumetric‐modulated arc therapy (VMAT) for head and neck cancers (HNC), either with a "standard" simultaneously integrated boost technique (S‐SIB) or with a "dose painting" SIB technique (DP‐SIB). HNC patients were planned either with an S‐SIB comprising three dose levels, from 56 to 70 Gy (16 patients), or with a DP‐SIB comprising five dose levels, from 56 to 84 Gy (8 patients), in 35 fractions. Two VMAT plans were calculated for each SIB technique using two Elekta MLCs: MLCi2 with 10 mm leaf width and Beam Modulator (BM) with 4 mm leaf width. Dose distributions were evaluated by comparing doses on PTVs, main OARs, and healthy tissue, and by comparing conformation indexes. Treatment efficiencies were evaluated by comparing the number of monitor units and the number of needed arcs. Comparisons of the two MLCs depending on the two SIB techniques showed: i) Regarding PTVs: Dmean and D2% on lower doses PTV decreased respectively by 0.5 Gy ( p = 0.01 ) and 0.9 Gy ( p = 0.01 ) with BM than with MLCi2 for S‐SIB; no significant difference was found for DP‐SIB; ii) Regarding OARs: for spinal cord and brainstem, D2% decreased respectively by 1.2 Gy ( p = 0.03 ) and 4.2 Gy ( p = 0.04 ) with BM than with MLCi2 for S‐SIB; for controlateral parotid, D50% decreased by 1.5 Gy ( p = 0.01 ) with BM than with MLCi2 for S‐SIB; iii) Regarding treatment efficiency : the number of monitor units was 44% ( p = 0.00 ) and 51% ( p = 0.01 ) higher with BM for S‐SIB and DP‐SIB, respectively. Two arcs were more frequently needed with BM to reach an acceptable dose distribution. This study demonstrated that Beam Modulator (4 mm leaf width) and MLCi2 (10 mm leaf width) MLCs from Elekta provided satisfactory dose distributions for treatment delivery with VMAT technique for complex HNC cases with standard and dose painting prescriptions. OAR sparing was better with BM, mainly for brainstem and spinal cord. However, delivery efficiency of VMAT plans was better with MLCi2. PACS numbers: 87.56.N‐, 87.56.nk, 87.55.D‐